Basal slip in Laves phases: The synchroshear dislocation. (June 2019) - Guénolé, Julien; Mouhib, Fatim-Zahra; Huber, Liam; Grabowski, Blazej; Korte-Kerzel, Sandra
Abstract: Two different mechanisms have been reported in previous ab initio studies to describe basal slip in complex intermetallic Laves phases: synchroshear and undulating slip. To date, no clear answer has been given on which is the energetically favourable mechanism and whether either of them could effectively propagate as a dislocation. Using classical atomistic simulations supported by ab initio calculations, the present work removes the ambiguity and shows that the two mechanisms are, in fact, identical. Furthermore, we establish synchroshear as the mechanism for propagating dislocations within the basal plane in Laves phases. Graphical abstract: Unlabelled Image